Development of E-LKPD Assisted by GeoGebra on Trigonometry Material to Support Students’ Understanding of Concepts In Grade XI - Avinda Dwi Sagita; Anita Dewi Utami (Universitas Islam Sultan Agung, 2025)
This study aims to design and develop GeoGebra-assisted E-LKPD learning media for trigonometry topics —tangent, cotangent, and reciprocal identities —to foster 11th-grade students' conceptual understanding. This study employed a Research and Development (R&D) approach using the ADDIE model. The research subjects consisted of 11th-grade students at SMAN 1 Batu. The data analysis techniques used in this study include validity, practicality, and effectiveness analysis. The analysis results indicate that this media is valid, with an average validity score of 3.85 and a material validity score of 3. . The practicality of this media is considered practical based on the student response questionnaire, which yielded an average score of . The effectiveness analysis of this media was based on students' essays on trigonometry material. A total of of students achieved scores above , thus meeting the effectiveness criteria. Therefore, it can be concluded that the GeoGebra-assisted E-LKPD developed is valid, practical, and effective, making it suitable as a mathematics learning medium to enhance students' conceptual understanding of trigonometry.Keywords: E-LKPD, GeoGebra, Trigonometry